(untitled) (Physical Education, Health and Social Sciences, 2024)
This study was undertaken to examine the association between cybervictimization, coping strategies, and resilience among social media users. The research employed a cross-sectional design and included 300 participants who maintained public profiles on online platforms, had more than 25,000 followers, and were between 17 and 30 years of age. The study variables were assessed through the Cyber Victimization Scale. The results indicated that cybervictimization had a significant negative association with coping strategies, while it showed a positive relationship with resilience. In addition, both emotion-focused coping and problem-focused coping were found to be significantly and positively linked with resilience. The findings further revealed that individuals involved in catfishing behavior were more likely to encounter both visual sexual victimization and cybervictimization. Significant mean differences were also observed across groups on the basis of age and gender. The study offers useful directions for future research and practical learning, while also supporting the design of media literacy initiatives, stronger online protection strategies, and awareness programs.